Korelasi Antara Volume dan Nilai Produksi Untuk Optimalisasi Usaha Penangkapan Ikan Pulau Panggang - Khoerunnisa, Nurani; Wijayanti, Siti Oftafia; Rema, Dareen Nadya (2339-1324, 2025)
The fisheries sector on Panggang Island contributes significantly to the local economy, but efforts to optimally increase fish production still face challenges. Fish production is one of the main factors in determining the economic value of fisheries, so it is essential to know the extent of the relationship between fish production volume and production value. This study aims to analyze this relationship using the Pearson correlation analysis approach, which measures the closeness of the linear relationship between the two variables. The results show that the volume of fisheries production has a very close and positive relationship with production value. The correlation coefficient value of fishing units on Panggang Island is above 0.9, namely fishing rods (0.98), traps (0.99), and nets (0.99), which indicates that increasing production volume directly affects increasing production value. Strategies for optimizing fisheries production include using efficient and environmentally friendly fishing technology, business planning based on feasibility analysis, managing fishing activities according to the season, expanding market access, and strengthening the supply chain. These findings form the basis for strategic decision-making in increasing the productivity and sustainability of the fisheries sector on Panggang Island.